Why Is It Too Cold? Towards a Mechanistic Understanding of Cold‐Water Pollution Effects on Recruitment of an Imperiled Warmwater Fish - Eliza I. Gilbert; Tracy A. Diver; Steven M. Mussmann; Melody J. Saltzgiver; William K. Knight; Scott L. Durst; Michael A. Farrington; Stephani L. Clark Barkalow; Michael Tobler; Nathan R. Franssen (Molecular Ecology, 2025)
Environmental temperature shapes the ontogeny of ectotherms by influencing rates of growth and development which can be key determinants of survival. Whereas the escalating impacts of water management on freshwater ecosystems is well documented, the effects of cold‐water releases from dams—which can alter downstream temperatures—remains relatively underexplored but may present novel challenges to endemic ectotherms. Specifically, little is known about how thermal depressions reshape phenotypic and genetic patterns during larval metamorphosis for fishes that evolved in warmwater systems. We assessed the effects of thermal shifts on larval ontogeny of the endangered razorback sucker ( Xyrauchen texanus ), which evolved in the warm waters of the Colorado River Basin, USA. We hypothesised that development is more sensitive to cold‐water influences than growth and that temperature would influence patterns in gene expression related to development. Our results supported these hypotheses and showed that both wild and laboratory‐reared larvae in slightly cooler temperatures exhibited delayed development, but similar growth compared to larvae reared in warmer conditions. These findings suggest growth and development in early ectotherm life stages can be decoupled, which follows patterns more like the temperature‐size rule than allometric scaling of development by size. We also observed transcriptional differences related to genes associated with stress responses and development in our laboratory‐reared fish; here, gene expression of fish from the coldest conditions at the end of the experiment was more similar to fish reared in warmer temperatures at the midpoint. Our findings suggest that modest temperature reductions can delay ontogeny and alter the transcriptional landscape while not necessarily limiting growth. This finding highlights the need for conservation practitioners to consider cascading impacts that even small temperature reductions can cause in riverine ecosystems.